AIR QUALITY TEST OF CIGARETTE SMOKE IN COFFEE SHOPS IN SOUTH ACEH - Erwinsyah Sipahutar; Rudi Arif Candra; Arie Budiansyah; Oktrison (Politeknik Aceh Selatan, 2025)
This study aims to analyze air quality in coffee shops in South Aceh using the MQ2 sensor to detect cigarette smoke. Cigarette smoke is a significant source of indoor air pollution and can negatively impact health. The MQ2 sensor was installed in various locations within the coffee shops to measure smoke concentration at different times, including peak and off-peak hours. The measurement results showed variations in cigarette smoke concentration, with peak levels occurring during times of increased customer traffic. Coffee shops with better ventilation systems exhibited lower smoke concentrations, indicating the importance of good air circulation in reducing the effects of cigarette smoke. These findings suggest the need for stricter regulations regarding smoking in public places and improvements in ventilation systems to protect the health of customers and staff. This research provides important insights into indoor air quality management and encourages the implementation of smoke-free policies in coffee shops. From the results of tests conducted in several coffee shops, it was found that the average cigarette smoke content increased in rooms with more than four fans, and that the size of the coffee shop had an influence.